2019
DOI: 10.1556/066.2018.0005
|View full text |Cite
|
Sign up to set email alerts
|

Preventing oxidation of canola and sunflower oils by addition of pomegranate seed oil

Abstract: The study was designed to explore the antioxidative effect of pomegranate seed oil (PSO) at different concentrations (5 and 7%) against oxidation of plant-based oils (canola oil and sunfl ower oil) during storage (60 days) as compared to artifi cial antioxidant butylated hydroxyanisole (BHA, 200 ppm). Rancimat and Schaal oven analysis were employed for the assessment of potential consequences of PSO against oxidation in plant based oils. The variation in total phenolic contents (TPC), antioxidant activity, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…From Figure 3b, it is apparent that the DPPH radical scavenging capacity of SO decreased at a faster rate than that of SO:PSO and SO:BPSO. The finding concurs with results from previous studies [26]. The reaction rate constants for the depletion of DPPH radical scavenging capacity in SO, SO:PSO, and SO:BPSO were 0.182, 0.111, and 0.119 mmol Trolox (n−1) •day −1 , respectively.…”
Section: Volatile Oxidation Compounds Concentration At the End Of Acc...supporting
confidence: 92%
See 1 more Smart Citation
“…From Figure 3b, it is apparent that the DPPH radical scavenging capacity of SO decreased at a faster rate than that of SO:PSO and SO:BPSO. The finding concurs with results from previous studies [26]. The reaction rate constants for the depletion of DPPH radical scavenging capacity in SO, SO:PSO, and SO:BPSO were 0.182, 0.111, and 0.119 mmol Trolox (n−1) •day −1 , respectively.…”
Section: Volatile Oxidation Compounds Concentration At the End Of Acc...supporting
confidence: 92%
“…The levels of α and δ-tocopherols in this study were lower, compared to literature, indicating losses during the GC-MS analysis. Lower levels of tocopherols in both SO (δ-tocopherols: 12.4 µg/g) and SO:PSO blend (δ-tocopherols: 13.2 µg/g) have been reported in similar studies [26]. The extraction efficiency of tocopherols may depend on the size, polarity of the tocopherols, and whether they exist as free or complexed molecules in the seed matrix [3].…”
Section: Total Phenolic Content Total Carotenoids Content and Tocophe...mentioning
confidence: 56%
“…Again, the RSA of the supplemented oil was 11 and 7-fold the values observed for the original oil, at the beginning and at the end of the accelerated oxidation test, respectively. Similarly, Siraj et al [39] studied the oxidative stability of canola and sunflower oil, supplemented with pomegranate seed oil, at 62 • C for 60 days and observed that the radical scavenging activity of the samples decreased during storage time. In the beginning of the experiment (day 0), the supplemented sunflower oil sample had an antioxidant activity of 52.71 ± 0.17 mg Trolox/kg, which decreased with the storage time and reached 20.02 ± 2.14 mg Trolox/kg after 12 days at 60 • C (62% reduction) (Figure 7).…”
Section: Accelerated Oxidation Testsmentioning
confidence: 96%
“…There are various reports in the literature showing the high phenolic and carotenoid contents of PSO [3,8,9]. Moreover, PSOs have been proposed as a more effective alternative to synthetic antioxidants to protect plant-based oils against oxidation [24].…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%